2019
DOI: 10.1111/andr.12620
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative global proteomics approach to understanding the functional pathways dysregulated in the spermatozoa of asthenozoospermic testicular cancer patients

Abstract: Background: Testicular cancer (TC) is the most common cancer diagnosed in men of reproductive age group. Sperm banking is recommended in these patients prior to cancer treatment. There is no literature describing the proteins dysregulated in the spermatozoa of TC patients with poor motility. Objective: The primary objective of this study was to compare the differences in the sperm proteome of normozoospermic (motility > 40%) and asthenozoospermic (motility < 40%) TC patients who had cryopreserved semen samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…A large clinical study from a semen bank confirmed that TGCT patients had decreased sperm concentration and total motile sperm count even before treatment (Xu et al , ). Similar findings are reported in another translational study, which followed these observations by comparing the proteomic profiles of spermatozoa from testicular cancer patients with asthenozoospermia and normospermia, and found quantitative changes in several proteins involved in mitochondrial function, oxidative phosphorylation and fertilisation (Panner Selvam et al , ).…”
supporting
confidence: 82%
“…A large clinical study from a semen bank confirmed that TGCT patients had decreased sperm concentration and total motile sperm count even before treatment (Xu et al , ). Similar findings are reported in another translational study, which followed these observations by comparing the proteomic profiles of spermatozoa from testicular cancer patients with asthenozoospermia and normospermia, and found quantitative changes in several proteins involved in mitochondrial function, oxidative phosphorylation and fertilisation (Panner Selvam et al , ).…”
supporting
confidence: 82%
“…In the current study, molecular functions associated with mitochondria were dysregulated in the spermatozoa of cancer patients, mainly due to the aberrant expression of the mitochondrial proteins. Earlier proteomic studies reported that sperm mitochondrial proteins were affected in cancer conditions such as testicular cancer [22,28] and Hodgkin's disease [23]. Based on our proteomic results, the oxidative phosphorylation, a process linked to mitochondrial function, was defective in the spermatozoa of cancer patients (irrespective of the type of cancer included in this study).…”
Section: Discussionsupporting
confidence: 60%
“…During the past decade, the proteomics platform was used to profile the proteins in seminal fluids of patients diagnosed with several types of cancers, such as prostate cancer [25][26][27], testicular cancer [21,22,28], Hodgkin's disease [23], and leukemia [24]. Based on their ability to detect the expression of thousands of proteins simultaneously, proteomics techniques are of great interest to unravel the molecular mechanisms leading to infertility in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations